Disordered eating, perfectionism and body-esteem of elite synchronized swimmers - Ferrand, C.; Magnan, C.; Rouveix, M.; Filaire, E. (European Journal of Sport Science, 2007)
The aims of the present study were to determine the extent to which unhealthy compensatory behaviours are observed in synchronized swimmers, and to examine the relationships between perfectionism, body-esteem dimensions, and restrained eating. Thirty-three elite adolescent synchronized swimmers completed the Multidimensional Perfectionism Scale (MPS-H), the Body-Esteem Scale, the Dietary Restraint Scale, and a self-report questionnaire during their pre-competitive period. The participants reported that they perceived themselves to be overweight, that they used weight loss methods such as self-induced vomiting, fasting, and intensive exercise, and unhealthy weight control behaviours such as skipping meals. The swimmers attributed the pressure to lose weight to team-mates, coaches, and themselves. Results showed that self-oriented perfectionism was significantly associated with dietary restraint and that body-esteem weight satisfaction has a mediator role between self-oriented perfectionism and dietary restraint. Additional research is required to examine the thrust of these results and the effectiveness of interventions that help prevent disordered eating patterns.